Haemothorax after subclavian vein cannulation. - Holt, S (1977)
A patient in whom pulmonary arterial bleeding occurred during percutaneous supraclavicular puncture of the subclavian vein is described. A retrospective survey of over 600 subclavian venepunctures disclosed seven patients in whom serious traumatic complications occurred, six of them in the hands of inexperienced operators.